Understanding L2 generalist teachers' motivation for teaching EFL in China's rural elementary schools - Sun, Wei; Shi, Hong (Frontiers in Education, 2024)
In the context of global mandates for English as a Foreign Language (EFL) education, rural regions face significant hurdles in delivering high-quality language instruction. Generalist teachers in these areas often lack specialized training in EFL, yet are tasked with its instruction. Referred to as L2 generalists, these educators hold a pivotal role in EFL education. However, a notable gap exists in understanding the motivation propelling generalist teachers to undertake EFL instruction, particularly within Chinese rural primary schools, where various challenges persist. Grounded in self-discrepancy theory and possible selves theory, this study examined the way L2 generalist teachers' teaching motivation linked to their various self-concepts and their responses to various challenges when delivering EFL teaching in rural elementary schools in China. The study uncovered that the alignment between L2 generalist teachers' ought selves (i.e., the selves that they believe they should be) and ideal selves (i.e., the selves they aspire to become) acted as motivating factors, guiding their active involvement in EFL teaching. However, challenges such as a lack of professionalization and high contextual expectations led to a discrepancy between their actual selves (i.e., the selves they perceive themselves to currently be) and their ought/ideal selves, diminishing their teaching motivation. Furthermore, the presence of ambiguous and conflicting school policies further complicated matters, confusing generalist teachers and eroding their teaching motivation. Despite experiencing a decline in motivation for EFL teaching, their commitment to their students fostered consistency between their ideal and ought selves, inspiring them to innovate pedagogical strategies within their capabilities.